Increasing running volume elicits hematological changes in trained endurance runners: a case study (El aumento del volumen de entrenamiento de carrera induce alteraciones hematológicas en corredores entrenados: un estudio de caso) - Rodrigues dos Santos, José Augusto (Retos, 2019)
Abstract. Background: Endurance running training induces several hematological changes that increase the capture, transport and delivery of the oxygen to the exercising muscles. Objective: This study aimed to verify how a dramatic increase in running volume induced new alterations in several hematological indicators in previously trained endurance runners. Methods: Three subjects (PL: 26 years, 169,5 cm; HP, 27 years, 167,9 cm; MC, 27 years, 180,7 cm) running 10-12 km/day, increased their running volume to prepare the participation in a 100-km ultra-marathon. New training program included 10-12 training sessions per week, totalizing 200-260 km. Average daily running volume was 35.8±6.2 km. The parameters analyzed were: hemoglobin, erythrocytes, hematocrit, mean cell volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), leukocytes, neutrophils, eosinophils, lymphocytes, and monocytes. Results: Erythrocyte count, hemoglobin, and hematocrit decreased 6.5%, 5.1% and 6.7%, respectively for the average of the three runners. Leukocytes, neutrophils, eosinophils, lymphocytes, and monocytes showed different alterations among participants with all the values remaining within normal reference values. Conclusion: Well-trained runners show further hematological alterations when training volume is dramatically increased, which can be seen as the specific adaptation to the new training level. It seems that hemogram is more sensitive than leucogram to the increase in running volume. Resumen. Antecedentes: El entrenamiento de resistencia aeróbica induce varios cambios hematológicos que aumentan la captura, el transporte y la entrega del oxígeno a los músculos en ejercicio. Objetivo: El objetivo de este estudio fue verificar cómo un aumento dramático en el volumen de corrida indujo nuevas alteraciones en varios indicadores hematológicos en corredores previamente entrenados. Métodos: Tres sujetos (PL: 26 años, 169,5 cm, HP, 27 años, 167,9 cm, MC, 27 años, 180,7 cm) corriendo 10-12 km / día, aumentaron su volumen de carrera para preparar la participación en un ultra maratón de 100 km. El nuevo programa de entrenamiento incluyó 10-12 sesiones de entrenamiento por semana, totalizando 200-260 km. El promedio diario de volumen de carrera fue de 35,8 ± 6,2 km. Los parámetros analizados fueron hemoglobina, eritrocitos, hematocrito, volumen celular medio (MCV), hemoglobina corpuscular media (MCH), concentración media de hemoglobina corpuscular (MCHC), leucocitos, neutrófilos, eosinofilos, linfocitos y monocitos. Resultados: El recuento de eritrocitos, la hemoglobina y el hematocrito disminuyeron 6,5%, 5,1% y 6,7%, respectivamente, para el promedio de los tres corredores. Los leucocitos, neutrófilos, eosinofilos, linfocitos y monocitos mostraron diferentes alteraciones entre los participantes con todos los valores restando dentro de los valores normales de referencia. Conclusión: Corredores bien entrenados muestran alteraciones hematológicas adicionales cuando el volumen de entrenamiento aumenta drásticamente, lo que puede ser visto como la adaptación específica al nuevo nivel de entrenamiento. Parece que el hemograma es más sensible que el leucograma al aumento en el volumen de entrenamiento de carrera.